2005
DOI: 10.1038/sj.ejcn.1602074
|View full text |Cite
|
Sign up to set email alerts
|

A 7-week reduction in salt intake does not contribute to markers of bone metabolism in young healthy subjects

Abstract: Background: Sodium intake increases urinary calcium excretion and may thus lead to negative calcium balance and bone loss. Objective: We hypothesised that reducing sodium intake would reduce urinary calcium excretion and have a beneficial influence in bone metabolism. Design: A total of 29 subjects, 14 males and 15 females, were divided into two study groups. One group (low-sodium group (LS)) reduced sodium intake for 7 weeks by substituting low-salt alternatives for the most important dietary sources of sodiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…This was accompanied by a lower urinary excretion of both sodium and calcium, but there were no changes in calcitropic hormones. Conversely, in younger men and women (21–39 yr of age) given a low salt diet for 7 wk, there were no detectable changes in markers of bone metabolism (34) . However, this was a parallel design study, which is not as robust as the cross‐over design used in this study.…”
Section: Discussionmentioning
confidence: 78%
“…This was accompanied by a lower urinary excretion of both sodium and calcium, but there were no changes in calcitropic hormones. Conversely, in younger men and women (21–39 yr of age) given a low salt diet for 7 wk, there were no detectable changes in markers of bone metabolism (34) . However, this was a parallel design study, which is not as robust as the cross‐over design used in this study.…”
Section: Discussionmentioning
confidence: 78%
“…Conversely, in a crossover trial of high versus low sodium intake for one week, no changes in bone resorption or calcium absorption were observed in 11 premenopausal women, although urinary calcium excretion increased [26]. Similarly, in a randomized seven-week trial of reduced sodium intake that included 15 young women (as well as 14 men), urinary sodium decreased but no group differences were seen in serum bone turnover markers [27]. The small sample sizes and short duration of these studies, however, may have limited their power.…”
Section: Discussionmentioning
confidence: 99%
“…Lin et al [6] reported that consumption of diets containing 3 levels of sodium (50, 100 and 150 mmol/day) increased parathyroid hormone (PTH), but did not significantly change serum concentrations of osteocalcin and C-terminal telopeptide of type 1 collagen in men and women. Other studies also reported that the effects of high sodium consumption on bone resorption were observed in postmenopausal women [11,23,24] , but not in younger adults or men [19,23,25,26] . These results were consistent with our study in that sodium excretion was negatively associated with bone mass in women, but not in men.…”
Section: Discussionmentioning
confidence: 95%